Managerial competency evaluation of vocational school principals in Magelang - Agnes Deswatun Khasanah; N. Nuchron (Jurnal Pendidikan Vokasi, 2018)
The purpose of this study was to discover the implementation of managerial competence of vocational school principals in Magelang from the perspective of (1) planning, (2) implementation, and (3) result. This study had a form of evaluation research with discrepancy method. The subjects of this study were four principals and thirty teachers of SMK Ma'arif 1 Ngluwar, SMK Ma'arif Salam, SMK Ma'arif Kota Mungkid, and SMK N 1 Salam. The data were collected using questionnaire and interview. This study used analysis of quantitative descriptive as analysis data method. The result of this study indicated that the planning of principals' managerial competence acquired from questionnaire was in "very good" category with average score 52.70; the implementation of vocational school principals' managerial competence in Magelang based on the questionnaire result was in "very good" category with the average score 127.25; and the result of vocational school principals' managerial competence in Magelang based on the questionnaire was in "very good" category with the average score 34.20.